Direct oxidation of H-2 to H2O2 over Pd-based catalysts: influence of oxidation state, support and metal additives - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
The influence of oxidation state (reduced and oxidized), support (ZrO2, Ga2O3, CeO2, SiO2, H-beta, ThO2, CeO2-ZrO2, BPO4 and Pd/Al2O3) and precious metal additives (Au, Pt, Rh and Ru) on the direct H2O2 synthesis has been investigated over Pd-based catalysts. For all the supports investigated herein, the oxidized Pd catalysts showed significantly superior H2O2 yields as compared to their reduced counterparts. The effect of the Pd oxidation state was found to be more important for determining the H2O2 yields than the particle size and surface area properties of the catalyst system. An excellent correlation was observed between the H2O2 selectivity and H2O2 decomposition activity of the oxidized Pd catalysts. The oxidized Pd catalysts showed almost an order of magnitude lower H2O2 decomposition activity than the reduced catalysts. The H2O2 yield in the H-2 to H2O2 oxidation passed through a maximum with increase in the An concentration. Although a similar effect was also observed in case of Pt, Au was found to be a superior promoter for the direct H2O2 synthesis process. Addition of Rh and Ru was found to be detrimental for the H2O2 yields; these results can be explained in terms of increased H2O2 decomposition activity and/or enhanced H-2 to H2O reaction activity in their presence. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: decomposition; direct synthesis; H2O2; metal additives; oxidation state; Pd catalysts; supports

Photocatalytic degradation of Azo dyes using Au:TiO2, gamma-Fe2O3:TiO2 functional nanosystems - Jagadale, Tushar C.; Kulkarni, Manjusha; Pravarthana, D.; Ramadan, Wegdan; Thakur, Pragati (Journal of Nanoscience and Nanotechnology, 2012)
We report photocatalytic degradation studies on Navy Blue HE2R (NB) dye on significant details as a representative from the class of azo dyes using functional nanosystems specifically designed to allow a strong photocatalytic activity. A modified sol-gel route was employed to synthesize Au and gamma-Fe2O3 modified TiO2 nanoparticles (NPs) at low temperature. The attachment strategy is better because it allows clear surface of TiO2 to remain open for photo-catalysis. X-ray diffraction, Raman and UV-VIS spectroscopy studies showed the presence of gold and iron oxide phases along-with the anatase TiO2 phase. TEM studies showed TiO2 nanocomposite particles of size similar to 10-12 nm. A detailed investigation on heterogeneous photocatalytic performance for Navy Blue HE2R dye was done using the as-synthesized catalysts Au:TiO2 and gamma-Fe2O3:TiO2 in aqueous suspension under 8 W low-pressure mercury vapour lamp irradiation. Also, the photocatalytic degradation of Amranth and Orange G azo dyes were studied. The surface modified TiO2 NPs showed significantly improved photocatalytic activity as compared to pure TiO2. Exposure of the dye to the UV light in the presence of pure and gold NPs attached TiO2 catalysts caused dye degradation of about similar to 20% and similar to 80%, respectively, in the first couple of hours. In the presence of gamma-Fe2O3 NPs attached TiO2, a remarkable similar to 95% degradation of the azo dye was observed only in the first 15 min of UV exposure. The process parameters for the optimum catalytic activity are established which lead to a complete decoloration and substantial dye degradation, supported by the values of the Chemical Oxygen Demand (COD) similar to 93% and Total Organic Carbon (TOC) similar to 65% of the treated dye solution after 5 hours on the employment of the UV/Au:TiO2/H2O2 photocatalytic process.
Keywords: Azo Dye; COD; H2O2; Photocatalysis; TiO2

Efficient electrochemical oxygen reduction to hydrogen peroxide by transition metal-doped silicate Sr0.7Na0.3SiO3-delta - Thundiyil, Shibin; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2021)
Electrochemical oxygen reduction in a selective two-electron pathway is an efficient method for onsite production of H2O2. State of the art noble metal-based catalysts will be prohibitive for widespread applications, and hence earth-abundant oxide-based systems are most desired. Here we report transition metal (Mn, Fe, Ni, Cu)-doped silicates, Sr0.7Na0.3SiO3-delta, as potential electrocatalysts for oxygen reduction to H2O2 in alkaline conditions. These novel compounds are isostructural with the parent Sr0.7Na0.3SiO3-delta and crystallize in monoclinic structure with corner-shared SiO4 groups forming cyclic trimers. The presence of Na stabilizes O vacancies created on doping, and the transition metal ions provide catalytically active sites. Electrochemical parameters estimated from Tafel and Koutechy-Levich plots suggest a two-electron transfer mechanism, indicating peroxide formation. This is confirmed by the rotating ring disc electrode method, and peroxide selectivity and Faradaic efficiency are calculated to be in the range of 65-82% and 50-68%, respectively, in a potential window 0.3 to 0.6 V (vs RHE). Of all the dopants, Ni imparts the maximum selectivity and efficiency as well as highest rate of formation of H2O2 at 1.65 mu mol s(-1).
Keywords: H2O2; mixed metal oxide; ORR; silicate

Hierarchical TS-1 for epoxidation of non-edible Karanja (Millettia pinnata) oil methyl ester to methyl epoxioleate (biodiesel additive) in presence of H2O2 as oxidizing agent - Anil, Reshma; Niphadkar, Prashant; Bokade, Vijay (Environmental Progress & Sustainable Energy, 2022)
Application of non-edible Karanja (Millettia pinnata) oil which is abundantly available in India is not explored so far. The present study is an attempt to convert fatty acid methyl ester (FAME) obtained from Karanja oil to methyl epoxioleate over hierarchical titanosilicate (TS-1) catalyst. Methyl epoxioleate, a biodiesel additive can blend up to 20% with biodiesels to improve oxidative stability and cold flow properties of biodiesel. A series of hierarchical TS-1 were prepared by desilication of parent TS-1 with 0.1 N NaOH at 80 degrees C for 1, 3, 5, and 7 h, respectively. Samples were characterized by powder XRD, low temperature nitrogen adsorption/desorption, and TEM. Eighty percent FAME conversion with 70% yield of methyl epoxioleate was obtained over 5H-TS-1 catalyst. The enhanced catalytic activity of a 5H-TS-1 compared to parent TS-1 mainly attributed to the high mesoporosity coupled with well-preserved crystallinity. 5H-TS-1 catalyst was found to be completely reusable after calcination at 500 degrees C for 12 h. Hierarchical 5H-TS-1 catalyst for effective conversion of non-edible Karanja oil methyl ester to methyl epoxioleate probably not reported so far.
Keywords: H2O2; hierarchical TS-1; Karanja oil methyl ester; methyl epoxioleate; TS-1